The Cost–Benefit of Federal Investment in Preventing Clostridium difficile Infections through the Use of a Multifaceted Infection Control and Antimicrobial Stewardship Program - Slayton, Rachel B. (Infect Control Hosp Epidemiol, 2015)
OBJECTIVE. To determine the potential epidemiologic and economic value of the implementation of a multifaceted Clostridium difficile infection (CDI) control program at US acute care hospitals DESIGN. Markov model with a 5-year time horizon PARTICIPANTS. Patients whose data were used in our simulations were limited to hospitalized Medicare beneficiaries ≥65 years old. BACKGROUND. CDI is an important public health problem with substantial associated morbidity, mortality, and cost. Multifaceted national prevention efforts in the United Kingdom, including antimicrobial stewardship, patient isolation, hand hygiene, environmental cleaning and disinfection, and audit, resulted in a 59% reduction in CDI cases reported from 2008 to 2012. METHODS. Our analysis was conducted from the federal perspective. The intervention we modeled included the following components: antimicrobial stewardship utilizing the Antimicrobial Use and Resistance module of the National Healthcare Safety Network (NHSN), use of contact precautions, and enhanced environmental cleaning. We parameterized our model using data from CDC surveillance systems, the AHRQ Healthcare Cost and Utilization Project, and literature reviews. To address uncertainty in our parameter estimates, we conducted sensitivity analyses for intervention effectiveness and cost, expenditures by other federal partners, and discount rate. Each simulation represented a cohort of 1,000 hospitalized patients over 1,000 trials. RESULTS. In our base case scenario with 50% intervention effectiveness, we estimated that 509,000 CDI cases and 82,000 CDI-attributable deaths would be prevented over a 5-year time horizon. Nationally, the cost savings across all hospitalizations would be $2.5 billion (95% credible interval: $1.2 billion to $4.0 billion). CONCLUSIONS. The potential benefits of a multifaceted national CDI prevention program are sizeable from the federal perspective.